2022
DOI: 10.1111/odi.14289
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of gingival recession: A systematic review and meta‐analysis

Abstract: ObjectiveThis systematic review and meta‐analysis aimed to estimate the global prevalence of gingival recession (GR) in the general population.Materials and MethodsPopulation‐based observational studies reporting the prevalence of GR and published from 1991 to 2021 were identified from five electronic databases and manual searches. Risk of bias was assessed using the Joanna Briggs Institute's Critical Appraisal Checklist for Prevalence Studies. The pooled prevalence of GR was calculated by using a random‐effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
1
1
0
2
Order By: Relevance
“… 34 It has also been linked with age in many studies. 35 However, in our study population, gingival recession was most prevalent in adults 18–38 years of age, which is also supported by a Brazilian study. 36 By contrast, a higher incidence of recession was seen in people with excellent oral hygiene than in those with poor oral hygiene.…”
Section: Discussionsupporting
confidence: 89%
“… 34 It has also been linked with age in many studies. 35 However, in our study population, gingival recession was most prevalent in adults 18–38 years of age, which is also supported by a Brazilian study. 36 By contrast, a higher incidence of recession was seen in people with excellent oral hygiene than in those with poor oral hygiene.…”
Section: Discussionsupporting
confidence: 89%
“…[ 2 ] It is a highly prevalent condition with varying patterns in different populations across the globe. [ 3 ] Several aspects of study design and clinical examination protocol can have an influence on its prevalence estimates. In addition, subject-related periodontal risk factors may further account for observed differences in the prevalence estimates across the studies.…”
Section: Introductionmentioning
confidence: 99%
“…Our recently published systematic review and meta-analysis on the worldwide prevalence of GR also revealed a conspicuous lack of homogeneity among the epidemiological studies and underscored the urgent need for a universally accepted standard protocol to report the GR prevalence. [ 3 ] Reporting of reliable data derived following standardized principles will not only facilitate the comparisons between GR prevalence estimates in different populations but would also help the public health policymakers in resource planning and sensitize the oral health-care personnel for early diagnosis, prevention, and need for interventional approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 The global prevalence of GR for buccal gingival recessions was reported as 75.42% in 2022. 2 Although GR can cause root sensitivity, root caries, and cosmetic issues, not all GR necessitate surgical intervention. However, untreated GR may result in progressive recession (odds ratio 2.43), which has a detrimental impact on the success of future treatment.…”
mentioning
confidence: 99%